Plasticity and modular control of locomotor patterns in neurological disorders with motor deficits - Ivanenko, Yuri P.; Cappellini, Germana; Solopova, Irina; Grishin, Alexander; MacLellan, Michael J.; Poppele, Richard; Lacquaniti, Francesco (Frontiers in Computational Neuroscience, 2013)
Human locomotor movements exhibit considerable variability and are highly complex in terms of both neural activation and biomechanical output. The building blocks with which the central nervous system constructs these motor patterns can be preserved in patients with various sensory-motor disorders. In particular, several studies highlighted a modular burst-like organization of the muscle activity. Here we review and discuss this issue with a particular emphasis on the various examples of adaptation of locomotor patterns in patients (with large fiber neuropathy, amputees, stroke and spinal cord injury). The results highlight plasticity and different solutions to reorganize muscle patterns in both peripheral and central nervous system lesions. The findings are discussed in a general context of compensatory gait mechanisms, spatiotemporal architecture and modularity of the locomotor program.